2019
DOI: 10.1016/j.jpeds.2019.02.021
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Vitamin D Supplementation Does Not Prevent Allergic Sensitization of Infants

Abstract: Objective To investigate the effect of vitamin D supplementation dose on allergic sensitization and allergic diseases in infants, and to evaluate whether vitamin D status in pregnancy and at birth are associated with infant allergy outcomes. Study design Altogether, 975 infants participated in a randomized, controlled trial of daily vitamin D supplementation of 10 mg (400 IU) or 30 mg (1200 IU) from the age of 2 weeks. At 12 months of age, food and aeroallergen IgE antibodies were measured, and the occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 32 publications
2
63
1
Order By: Relevance
“…Our finding of no statistically significant effect between vitamin D supplementation and medically diagnosed allergic disease over the first 2.5 years of age is consistent with other intervention trials which have been performed investigating the effect of maternal vitamin D supplementation during pregnancy and offspring allergic disease outcomes [15][16][17][18]. Even more importantly, our findings are also consistent with those in the recent infant RCT by Rosendahl et al [25], where they also found no statistically significant differences in allergic disease outcomes at 1 year between two groups of infants supplemented daily with either 10 (400 IU) or 30 µg (1200 IU) vitamin D from the age of 2 weeks. While our trial investigated the effect of the Australian recommended dose (400 IU) [26] for vitamin D supplementation in infancy versus placebo on allergy outcomes in early childhood, the study by Rosendahl et al was based on a secondary analysis comparing two different supplemental doses of vitamin D on allergy outcomes in the first year of life.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our finding of no statistically significant effect between vitamin D supplementation and medically diagnosed allergic disease over the first 2.5 years of age is consistent with other intervention trials which have been performed investigating the effect of maternal vitamin D supplementation during pregnancy and offspring allergic disease outcomes [15][16][17][18]. Even more importantly, our findings are also consistent with those in the recent infant RCT by Rosendahl et al [25], where they also found no statistically significant differences in allergic disease outcomes at 1 year between two groups of infants supplemented daily with either 10 (400 IU) or 30 µg (1200 IU) vitamin D from the age of 2 weeks. While our trial investigated the effect of the Australian recommended dose (400 IU) [26] for vitamin D supplementation in infancy versus placebo on allergy outcomes in early childhood, the study by Rosendahl et al was based on a secondary analysis comparing two different supplemental doses of vitamin D on allergy outcomes in the first year of life.…”
Section: Discussionsupporting
confidence: 92%
“…In our RCT and in that of Rosendahl et al [25], both involving infants born at term gestation, we did not find any significant benefit of infant vitamin D supplementation on reducing the incidence of medically diagnosed wheeze at 1 year of age. This contrasts with the results at 1 year of age from a recently published paper by Hibbs et al [29], where preterm black infants (mean gestational age of 33 weeks) were randomized to vitamin D supplementation of 400 IU/day until 6 months of age, and were found to have reduced recurrent wheezing (relative risk 0.66; 95% CI 0.47 to 0.94) compared with a placebo.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Some trials have also reported reduced development of wheeze or asthma, but not respiratory tract infections, in offspring of pregnant women supplemented with vitamin D; this effect was independent of starting 25(OH)D levels. The outcomes of trials of vitamin D supplementation to prevent allergic sensitization in infants are, however, controversial, with some trials reporting no significant benefits [ 47 ].…”
Section: Evidence For Health Benefits Of Sun Exposurementioning
confidence: 99%